Control performance assessment of cable-MR damper system based on pole assignment theory. (October 2022) - Huang, H.W.; Sun, L.M.
Abstract: Semi-active MR dampers have been proposed for cable vibration mitigation of long stay cables, relative theoretical and experimental studies have been carried out in the literature, and have been installed in some of the long span cable-stayed bridges for engineering practice. However, the actual efficiency of the semi-active control of cable-MR damper system has yet to be verified, which is important in real engineering practice. In this paper, the pole assignment theory is used and the corresponding numerical studies is carried out to verify the efficiency of the proposed semi-active control system. The simulation results show that MR damper using semi-active control is more efficient than using passive control and the semi-active control of cable-MR damper system could achieve the optimal control effect and better control efficiency of the system. This paper investigates the efficiency and effectiveness as well as the applicability of the proposed optimal control algorithm using MR damper for mitigating cable vibrations, which is important in real engineering practice.